HLA-DQB1*0301 in Bullous Pemphigoid and Pemphigus Vulgaris: A Meta-Analysis - Dylan Thibaut; Ryan Witcher; Breana Barnes; Kersten T. Schroeder (University Library System, University of Pittsburgh, 2023)
Background: The linkage of HLA-DQB1*0301 to autoimmune disorders is becoming more common in literature. Despite bullous pemphigoid (BP) and pemphigus vulgaris (PV) both having similar symptoms, such as blistering skin conditions, research has shown different relationships with HLAs. Methods: In this systematic review, HLA-DQB1*0301 and the odds of developing BP and PV were explored. Google Scholar and Pubmed were consulted, and articles were included if living subjects were used, odds ratio was available or could be ascertained from the study, and if it was not a meta-analysis of other researcher's works. MetaXL software was used to generate data for analysis and a forest plot was generated for each. Nine studies conducted between 1996 and 2021 met study selection criteria for the BP HLA-DQB1*0301 meta-analysis (1,340 patients and 6,673 controls) and five studies (247 patients and 2,435 controls) for PV. Results: HLA-DQB1*0301 increased the odds of developing BP (OR= 1.64, 95% CI [1.44, 1.87], I2= 0%) yet decreased odds of PV (OR= 0.60, 95% CI [0.40, 0.89], I2= 34%). Conclusion: Results suggest HLA-DQB1*0301 may serve opposite roles in BP and PV despite similarity in symptoms, finding higher odds for developing BP versus lower odds for developing PV. Understanding this HLA's function in each requires further exploration. Limitations of the analysis included minor asymmetry in the PV Doi plot, suggesting publication bias. No funding was used; study protocol was not registered.